THE DIAGNOSTIC VALUE OF FINE NEEDLE ASPIRATION CYTOLOGY IN MASSES OF THE SALIVARY GLANDS - Iqbal, Mahid; Anwar, Khurshid; Ullah, Ihsan; Javed, Muhammad; Khan, Iftikhar Ahmad; Hussain, Gulshan (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the sensitivity and specificity of fine needle aspiration cytology in masses of the Methodology: The study included 49 cases. It was conducted at the Departments 0f ENT, Hayatabad Medical Complex, Peshawar and Saidu Teaching Hospital, Saidu Sharif, Swat from January 1, 2002 to December 31, 2009. Patients undergoing Fine Needle Aspiration Cytology followed by open biopsy were included in the study. The results obtained on FNAC were compared with those obtained on biopsy findings of the respective specimens and the specificity and sensitivity of FNAC were calculated from the data. Results: The FNAC findings in salivary glands were; Benign 38, Malignant 7 and Suspicious 4. The biopsy findings were; Benign 33 and Malignant 16. Comparison of FNACs and biopsy in the salivary glands taken as True Negative, True positive, False Negative and False Positive respectively was; 32, 10, 6 & 1. The Sensitivity and Specificity for FNAC were calculated at 62.50% & 96.97% respectively. Conclusion: The results of this study show that FNA cytologic diagnoses in the salivary gland tumours are reliable and treatment can be planned on its basis. However, owing to a higher number of false negative cases occurring in this study, it is recommended that a negative cytology report should be viewed with suspicion. The diagnosis should be confirmed by open biopsy if clinical suspicion persists. various salivary glands.